Periodontal pockets: A potential reservoir for SARS-CoV-2?. (October 2020) - Badran, Zahi; Gaudin, Alexis; Struillou, Xavier; Amador, Gilles; Soueidan, Assem
Abstract: Periodontal pockets are the major clinical manifestation of Periodontitis, a chronic inflammatory oral disease affecting the teeth-supporting tissues and has high prevalence in the adult population. Periodontal pockets are ideal environments for subgingival bacterial biofilms, that interact with the supragingival oral cavity, mucosal tissues of the pocket and a peripheral circulatory system. Periodontal pockets have been found to harbor viral species such as the Herpes simplex viruses' family. Recently, the SARS-CoV-2 has gained major interest of the scientific/medical community as it caused a global pandemic (Covid-19) and paralyzed the globe with high figures of infected people worldwide. This virus behavior is still partially understood, and by analyzing some of its features we hypothesized that periodontal pocket could be a favorable anatomical niche for the virus and thus acting as a reservoir for SARS-CoV-2.